Four Validities as Pathways to Scientific and Societal Impact in Environmental Psychology - Kause, Astrid; Majer, Johann; Brick, Cameron (Environmental Psychology Open, 2026)
Environmental psychology researchers are often urged to increase their scientific and societal impact to combat climate change and related sustainability challenges. However, there is not much advice for how scholars can enhance their impact. Here, we propose that four well-established validities serve as guiding principles for enhancing impact: construct validity, internal validity, external validity, and statistical conclusion validity. We explain how these validities apply to environmental psychology research and outline the key validity threats that reduce both scientific as well as societal impact. Based on the interdisciplinary methodological literature from psychology and related fields, we provide strategies for boosting impact. Those strategies can be used by researchers, journal editors, funding agencies, and practitioners for evaluating and increasing both types of impact.